2010
DOI: 10.1007/s11095-010-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Histidine-Rich Amphipathic Peptides for siRNA Delivery

Abstract: The LAH4 histidine-rich cationic amphipathic peptides represent an interesting and promising family of compounds for siRNA delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 32 publications
4
115
1
Order By: Relevance
“…These data underline the fact that these two functions likely rely on different critical molecular determinants. Cell Line Transfection with Vectofusin-1 Derivatives-LAH4 derivatives have been described previously as nucleic acid transfection agents (31)(32)(33)43). Therefore, we tested the capacity of Vectofusin-1 and some derivatives to transfect 293T cells with an eGFP-expressing plasmid.…”
Section: Evaluation Of Vectofusin-1 Activity On Lentiviral Transductimentioning
confidence: 99%
“…These data underline the fact that these two functions likely rely on different critical molecular determinants. Cell Line Transfection with Vectofusin-1 Derivatives-LAH4 derivatives have been described previously as nucleic acid transfection agents (31)(32)(33)43). Therefore, we tested the capacity of Vectofusin-1 and some derivatives to transfect 293T cells with an eGFP-expressing plasmid.…”
Section: Evaluation Of Vectofusin-1 Activity On Lentiviral Transductimentioning
confidence: 99%
“…In an acidic environment, peptides are released from the complexes and change their conformation enabling membrane destabilising activity. Subsequently, nucleic acids are released from the endosomal/ lysosomal compartments into the cytoplasm [15,17]. Our previous study has demonstrated that the pH responsive peptides are capable of mediating both highly efficient DNA or siRNA transfection in mammalian cell lines [15] (Abbate et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, more recent investigations show that derivatives of LAH4 exhibit potent antimicrobial action against a number of pathogens found in clinical environments, and these activities are quite pronounced when the peptides occur in orientations parallel to the membrane surface . Furthermore the LAH4 sequences are also capable to transport big hydrophilic cargo such as DNA and RNA across the hydrophobic interior of membranes and thereby exhibit potent transfection capacities (Kichler et al, 2003;Langlet-Bertin et al, 2010;. Because of these important biological activities the thermodynamics of the peptides' interactions with membranes and nucleic acids were investigated in considerable detail and these investigations shall be presented in the following.…”
Section: The Lah4 Family Of Peptidesmentioning
confidence: 99%
“…Furthermore, it was recently shown that they are potent siRNA delivery vehicles with efficiencies that are higher than those of several well-established compounds such as Lipofectamine, DOTAP and polyethylenimine (Langlet-Bertin et al, 2010). In our laboratory a number of biophysical investigations have been performed, supported by many biochemical studies by our longstanding collaborators, which aimed at understanding the mechanisms of these transfection activities.…”
Section: Interactions Of Lah4 Peptides With Dnamentioning
confidence: 99%